2014
DOI: 10.1161/strokeaha.114.006348
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of Death-Associated Protein Kinase 1–p53 Interaction Exerts the Therapeutic Effects Against Stroke

Abstract: D eath-associated protein kinase 1 (DAPK1) is a Ca 2+ / calmodulin-dependent kinase 1 and plays roles in several modes of cell death in ischemic stroke. 2,3 To define a promising target that allows a delayed intervention being clinically effective against stroke, we searched for cell death signals downstream of DAPK1. We identified a direct binding of DAPK1 to a DNA-binding motif (DM) of the tumor suppressor protein p53 (p53DM), which is known as a transcriptional regulator of genes that control cell necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The DAPK1 protein has been shown to interact with extra-synaptic NMDA receptors containing the NR2B subunit, a process that is thought to induce and/or exacerbate injurious calcium influx (Tu et al, 2010). In addition, activated DAPK1 is associated with other signalling pathways linked to ischaemic cell death Wang et al, 2014). TAT-NR2Bct competitively inhibits activated DAPK1 binding to the NR2B subunit protein and thereby blocks subsequent downstream damaging cellular events caused by NMDA receptor over-activation.…”
Section: Nr2bct and Tat-nr2bct Peptidesmentioning
confidence: 99%
“…The DAPK1 protein has been shown to interact with extra-synaptic NMDA receptors containing the NR2B subunit, a process that is thought to induce and/or exacerbate injurious calcium influx (Tu et al, 2010). In addition, activated DAPK1 is associated with other signalling pathways linked to ischaemic cell death Wang et al, 2014). TAT-NR2Bct competitively inhibits activated DAPK1 binding to the NR2B subunit protein and thereby blocks subsequent downstream damaging cellular events caused by NMDA receptor over-activation.…”
Section: Nr2bct and Tat-nr2bct Peptidesmentioning
confidence: 99%
“…Our previous work demonstrated that following stroke, DAPK1 in the postsynaptic domain phosphorylated NMDA receptor NR2B at Serine-1303, eventually leading to neuronal death ( Tu et al 2010 ). Recently, we found that DAPK1 could also phosphorylate p53 at Serine-23 via direct binding of the DAPK1 death domain (DD) to the DNA-binding motif of p53 (p53DM) ( Pei et al 2014 ; Wang et al 2014 ). Though a handful of DAPK1 substrates have been identified, downstream signaling of DAPK1 that specifically mediates early spine damage after ischemic injuries is yet to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Using yeast two-hybrid analysis and GST affinity binding assay, the authors confirmed that DAPK1DD is bound to a p53 DNA-binding motif consisting of amino acids 241-281 (p53DM ) [48]. The application of a synthesized membrane-permeable p53DM 241-281 peptide (Tat-p53DM) that interrupts DAPK1-p53 interaction blocks these dual pathways of pS23 actions in vitro and in vivo [54]. Thus, the DAPK1-p53 interaction is a signaling point of convergence of necrotic and apoptotic pathways and is a desirable target for the treatment of ischemic insults.…”
Section: Dapk1 and P53mentioning
confidence: 92%